TÜRKÇE ÖĞRETMEN ADAYLARININ TEKNOLOJİK PEDAGOJİK ALAN BİLGİSİ DURUMLARININ ÇEŞİTLİ DEĞİŞKENLERLE İLİŞKİSİ. - DEMİR ATALAY, Tazegül (Electronic Turkish Studies)
This study aims to determine what level of technological pedagogical content knowledge (TPCK) of Turkish teacher candidates and to examine the relationship between the levels of technological pedagogical content knowledge of students with different variables. The research that want to put the current situation was carried out by descriptive research model of quantitative research methods. The study was conducted with a total of 264 students who are studying at 1st, 2nd, 3rd and 4th grade in Turkish education department of the Caucasus University Faculty of Education in 2015-2016 spring semester. Data of the research were obtained using the personal information form and Technological Pedagogical Content Knowledge Scale (TPCKS) which was adapted to Turkish by Şahin (2011). Data obtained from scales and information of participants were analyzed by SPSS (Statistical Package for the Social Sciences) 20.0 package program. According to the research findings, the following conclusions were reached: Prospectives of teacher candidates for level of technological knowledge for themselves are quite high. in terms of statistical area the arithmetic averages are considered that students stated that they have a little less information than medium level for technological knowledge and pedagogical content knowledge. According to gender variable a significant difference shows up within technological knowledge, pedagogical knowledge, technological content knowledge and pedagogical content knowledge. This difference is in favor of men in all dimensions. A significant difference according to the situation of teachers have their own computer shows up within technological knowledge, pedagogical knowledge, technological content knowledge and pedagogical content knowledge. Consider the arithmetic means the difference is in favor of the students said yes. A significant difference according to easy access to the internet situation variable of teacher candidates shows up within technological knowledge, pedagogical knowledge, technological content knowledge and pedagogical content knowledge. This difference is favor of the students who can easily enter the internet. According to the situation of mother's education content knowledge of teacher candidates formed a significant difference and this difference is favor of illiterate between illiterate with graduated of primary and high school, is favor of primary school graduate mothers between primary school graduate mothers with high school graduate mother, is favor of college graduate mothers between high school graduate mothers with college graduate mother. According to the scale of technological pedagogical content knowledge class variable determined a significant difference in all dimensions. In almost all the dimensions of this difference is in favor of classes 3 and 4. Father education and graduated high school variables did not cause any significant differences in the dimensions.